INSTALASI SISTEM OPERASI BERBASIS WINDOWS 10 PADA SEKOLAH MAN KISARAN - Ruri Ashari Dalimunthe; Riki Andri Yusda; William Ramdhan (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2020)
Abstract: Community service activities entitled "Installation of Operating Systems Based on Windows 10" aims to provide information to students from MAN Asahan about Installing Windows Operating Systems. The method used in this activity is a direct observation of the MAN Asahan school by watching and analyzing the problems or troubleshooting that occurs at the Computer Lab at MAN Asahan. In addition, information on problems in the computer Labs of the school was also carried out by a team of lecturers as the perpetrators of this community service by way of direct interviews with the Teachers and employees who served in the Computer Lab of the MAN Asahan school. The end result of this dedication is how students can repair computers, as well as troubleshooting that occurs on school computers and computers at home, can be overcome alone without having to use computer repair services.Keywords: installation; operating system; Windows 10 Abstrak: Kegiatan pengabdian kepada masyarakat yang diberi judul “Instalasi Sistem Operasi Berbasis Windows 10” bertujuan untuk memberikan informasi kepada siswa dan siswi MAN Asahan tentang Instalasi Sistem Operasi Windows. Metode yang digunakan dalam kegiatan ini adalah observasi langsung ke sekolah MAN Asahan dengan melihat serta menganalisa permasalahan ataupun troubleshooting yang terjadi pada Laboratorium Komputer disekolah MAN Asahan. Selain itu, Informasi permasalahan pada komputer Lab sekolah juga dilakukan tim dosen selaku pelaku kegiatan pengabdian ini dengan cara wawancara langsung kepada Guru dan pegawai yang bertugas di Lab Komputer sekolah MAN Asahan. Hasil akhir dari pengabdian ini adalah bagaimana siswa dan siswi dapat memperbaiki komputer serta troubleshooting yang terjadi pada komputer sekolah maupun komputer dirumah dapat teratasi sendiri tanpa harus memakai jasa perbaikan komputer. Kata kunci: instalasi; sistem operasi;  windows 10